Protein timing for the strength/power athlete - Hoffman, J. R. (EWF Scientific Magazine, 2017)
One of the benefits associated with protein consumption following an intense resistance training session is in its ability to enhance the recovery and remodeling processes within skeletal tissue (Tipton et al. 2004). A number of investigations have reported an attenuation in the extent of muscle damage, force decrements, and an enhanced recovery from protein ingestion following resistance exercise (Hoffman et al. 2010; Hulmi et al., 2009; Kraemer et al. 2006; Ratamess et al. 2003). In addition, when protein is consumed prior to, and immediately following a bout of resistance exercise an increase in messenger RNA (mRNA) expression is observed (Hulmi et al.2009). This is thought to accelerate muscle adaptation and enhance muscle recovery from the training session. Thus, timing of protein ingestion appears to take on greater importance in stimulating muscle adaptations that occur during resistance training programs. This review will focus on the acute effects of protein timing and then direct its attention to the potential benefits arising from the chronic effects of protein ingestion surrounding the training session